Evaluation of Pangasius pond sediment potentials in vegetable production as rooftop Bag Gardening (Journal of the Bangladesh Agricultural University, 2016)
An experimental research was carried out to assess the potential of Pangasius pond sediment (PPS) on the performance of yield and yield quality attributes of vegetable crop (BARIs tomato variety) grown in bag gardening system on rooftop under integrated aquaculture-horticulture approach. For this purpose, PPS chemical analysis, recording of plant morphological parameters and biochemical analysis of yield were performed. The plants were grown in 100% PPS =T1; 50% PPS + 50% Virgin soil (VS) = T2; and 60% VS + 40% Cowdung + 50g TSP + 50g MoP = T3. To compare with PPS treated treatments, treatment T3 was considered as control because it is a standard and recommended fertilizing dose of BARIs tomato production. The PPS sediments were collected from different aged ponds ranging from 1to 5 years Pangasius culture. The old PPS was used in bag gardening for the determination of soil physico-chemical, plant morpho-physiological and production parameters. All PPS in bags were belonged to silt loam in texture. The total nitrogen level was higher in T1 where 100% PPS was used. The T1 had the plant height 77.98 cm, number of leaves per plant 184.33, leaf area 622.49 cm2, which were significantly (p